Effect of Early Interactions With the Police on Intertemporal Choice: A Longitudinal Study of Zurich Public School Students - Deitzer, Jessica R. (Crime & delinquency, 2025)
Adolescents tend to increase their offending after police contact, contrary to predictions of choice-based theories. This may be due to police contact altering their view of their future prospects, leading them to prioritize the present. Preregistered fixed effects analyses of longitudinal data collected from Zurich public school students provide no support for an association between police contact and a change in impulsivity, sensation-seeking, or future orientation. Exploratory analyses find evidence that first-time and especially early contact with the police is associated with an increase in sensation-seeking and a reduction in future orientation. We conclude that certain types of police contact may increase young adolescents’ preference for the present. Future research should test whether this relationship is causal and generalizable.